Surviving the Crisis Through Collective Organizations in Rural Romania - Petrescu, Claudia (Calitatea Vieții, 2014)
In recent years, there has been a growing interest in developing associations and cooperatives in general amid flourishing policy debates on social economy and social enterprises. This paper will address the key challenges social economy entities are facing in rural areas of Romania through a comprehensive approach based on theoretical and empirical research. The paper will try to map social economy entities in rural Romania, focusing on the profile, structure and dynamics of these collective organizations, and thus completing the insufficient information available on alternative organizations in Romania and in Central and Eastern Europe in general. This paper is based on the data about social economy actors in Romania that we have used to compare social economy actors (cooperatives, associations, commons, NGOs). The purpose of this paper is to present and examine the role that social economy entities play in rural development in Romania. A core role in local development processes in Romania is played by NGOs which create innovative programs, services and activities in order to resolve the social problems and respond to social needs. These innovative programs, services and activities change the resources, beliefs, authorities and population perception. The type of services provided by the social economy entities, the effects thereof on the community (social inclusion of vulnerable groups, the creation of new participative development mechanisms, the creation of social infrastructure, the increase of social, human, symbolic capital, etc) determine the major role such entities play within the local development process. The main effects of the activity of these collective organizations over the local development are related to the increase of the social capital (the increase of the faith between the members and inside the institutions, the creation of more powerful relations among the members, the creation of networks with other communities), the stimulation of innovation and the introduction of these innovations in the activity of the local institutions, the increase of the occupancy rate, especially for the people in vulnerable groups, the formation of local development structures (action groups, initiative groups, community centres), the stimulation of the local development potential.